Pd-Catalyzed Oxidation of Aldimines to Amides - Gao, Shanshan; Ma, Yaorui; Chen, Weidong; Luo, Junfei (Synlett, 2018)
Methods for the synthesis of amides via the direct oxidation of imines are rarely reported. Here we report an efficient method for Pd-catalyzed oxidation of imines to amide derivatives by the use of cheap aqueous tert-butyl hydroperoxide as an oxidant through a Wacker-type reaction. This method is practically convenient and displays high functional group tolerance, allowing a variety of imines to transform into the corresponding amide derivatives in moderate to good yields.
Keywords: Pd-catalyzed; amides; imines; oxidation; tert-butyl hydroperoxide